Utilization of Pandan Leaf Extract (Pandanus Amaryllifolius) in Edible Film Substitute for Ready-to-Brew Coffee Packaging and Gives the Taste of Pandan Coffee - St Aisyah Khofifah Natsir; Lahming; Reski Febiyanti Rauf (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the panelists' preference for coffee packaged with edible film, the level of microbial contamination, and the characteristics of the edible film. This study is a quantitative study (experimental) using a completely randomized design (CRD) consisting of 4 treatments with 3 replications, namely control, 5% pandan, 10% pandan, and 15% pandan. Parameters observed included hedonic tests (color, scent, taste, and texture), microbial contamination tests (Mold/Yeast), and Edible film characteristics. The data obtained from the results of this study were analyzed using SPSS software with the technique of analysis variance (ANOVA) followed by Duncan's further test. The results showed that the addition of 15% pandan extract was the most preferred edible film by panelists and the best treatment in inhibiting the growth of microbes on the edible film, as well as affecting the characteristics of the edible film (tensile strength, elongation, solubility, and thickness).